Muslim rulers and rebels : everyday politics and armed separatism in the southern Philippines - McKenna, Thomas M., 1952- (Comparative studies on Muslim societies ;, 1998)
In this account of the Muslim separatist rebellion in the Philippines, Thomas McKenna challenges prevailing anthropological analyses of nationalism as well as their underlying assumptions about the interplay of culture and power. He examines Muslim separatism against a background of more than four hundred years of political relations among indigenous Muslim rulers, their subjects, and external powers seeking the subjugation of Philippine Muslims.